Overview of Pregnant Women's Knowledge of Antepartum Care at the Taraju Community Health Center in Tasikmalaya - Siti Rosita; Aulia Ridla Fauzi; Ima Sukmawati; Sri Utami Asmarani; Rosidah Solihah; Yanti Srinayanti; Sri Wulan Ratna Dewi; Metty Nurherliyany; Ayu Endang Purwati; Sandriani Sandriani (INDOGENIUS, 2025)
Background: Pregnancy begins with the meeting of the ovum and sperm cells will last around 9 months from the first day of the last menstruation, one of the important treatmens during pregnancy is a pregnancy check-up, which is a service provided by nurses to women during pregnancy, which monitors their physical dan psychological health, fetal growth, and preparation for childbrith. Apart from that, good knowledge about personal and fetal health care during pregnancy can improved the health of pregnant women. This research aims to assess the level of knowledge of pregnant women about antenatal care at the Taraju Tasikmalaya Community Health Center. Methods: this research method used was descriptive quantitative, with 30 respondents selected by accidental sampling, with data accumulation carried out using a questionnaire. Results: the result of the study showed that the majority of pragnant women at the Taraju Tasikmalaya Community Health Center had good knowledge about antenatal care at 66.7% (20 respondents), sufficiendt knowledge at 30% (9 respondents) or less at 3.3% (1 respondets). Conclusion: the majority of pregnant women’s knowledgeable about antenatal care at the Taraju Tasikmalaya Health Center for the period May to June 2024 mostly good.